2018
DOI: 10.1038/s41386-018-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

An unsuspected role for organic cation transporter 3 in the actions of amphetamine

Abstract: Amphetamine abuse is a major public health concern for which there is currently no effective treatment. To develop effective treatments, the mechanisms by which amphetamine produces its abuse-related effects need to be fully understood. It is well known that amphetamine exerts its actions by targeting high-affinity transporters for monoamines, in particular the cocaine-sensitive dopamine transporter. Organic cation transporter 3 (OCT3) has recently been found to play an important role in regulating monoamine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 50 publications
7
49
0
Order By: Relevance
“…; Mayer et al . ). Amphetamine‐induced DA release was significantly smaller in the SNc compared to previous FSCV measurements of amphetamine‐induced release in the striatal slices (Jones et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Mayer et al . ). Amphetamine‐induced DA release was significantly smaller in the SNc compared to previous FSCV measurements of amphetamine‐induced release in the striatal slices (Jones et al .…”
Section: Discussionmentioning
confidence: 97%
“…In peripheral cells, uptake of Met is mediated by the organic cation transporters OCT1 and OCT3 [ 37 , 38 , 39 ]. OCT3 is also found to be expressed in neurons [ 40 , 41 , 42 ]. Little is known about the expression pattern of Met transporters in the brains.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies with an OCT3-specific antibody have revealed that the transporter is expressed throughout the rat brain, with at least low levels of expression detected in nearly all brain regions (Gasser et al, 2009). The transporter is expressed in neurons (Cui et al, 2009;Graf et al, 2013;Hill and Gasser, 2013;Shang et al, 2003;Vialou et al, 2004), including dopamine neurons (Mayer et al, 2018), and glial cells, including astrocytes (Cui et al, 2009;Takeda et al, 2002) and microglia (He et al, 2017). It is also expressed in oligodendrocytes (Gasser et al, 2009), ependymal cells (Gasser et al, 2006;Gasser et al, 2009), and vascular endothelial cells in the brain (Li et al, 2013).…”
Section: Cellular and Subcellular Localization Of Oct3mentioning
confidence: 99%
“…Similarly, this review focused on our studies examining OCT3-mediated dopamine transport as it relates to the neurochemical and behavioral effects of cocaine. There is a growing body of work examining roles for OCT3mediated dopamine transport in the actions of other psychostimulant drugs, including amphetamine (Mayer et al, 2018;Vialou et al, 2008) and methamphetamine (Cui et al, 2009;Kitaichi et al, 2003;Nakayama et al, 2007). Clearly, many questions remain to be answered about the roles played by OCT3 and the other uptake 2 transporters in regulating monoamine signaling throughout the brain (Gasser and Daws, 2017).…”
Section: Corticosterone and The Regulation Of Cocaine-seeking Behaviomentioning
confidence: 99%